VAT Policy Reform in South Africa: An Equitable Redress to Income Inequality - Mabunda, Sibongiseni Sharon-rose (University of the Witwatersrand, Johannesburg, 2022)
The purpose of this research report is to discuss how VAT reform can reduce inequality and bridge the gap between the rich and the poor. It comprises a review of quantitative and qualitative evidence and provides an overview of VAT as a consumption tax and its role in the economy and social equity.
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce (specializing in Taxation) Johannesburg, 2022
Keywords: VAT Reform; Equity; Vertical Equit; Horizontal Equity; Inequality; UCTD; Income Inequality; Taxpayer; Income Redistribution; Tax Incidence or Tax Burden; SDG-8: Decent work and economic growth; SDG-10: Reduced inequalities